Dystroglycan controls dendritic morphogenesis of hippocampal neurons in vitro - Bijata, Monika; Wlodarczyk, Jakub; Figiel, Izabela (Frontiers in Cellular Neuroscience, 2015)
Dendritic outgrowth and arborization are important for establishing neural circuit formation. To date, little information exists about the involvement of the extracellular matrix (ECM) and its cellular receptors in these processes. In our studies, we focus on the role of dystroglycan (DG), a cell adhesion molecule that links ECM components to the actin cytoskeleton, in dendritic development and branching. Using a lentiviral vector (LV) to deliver short-hairpin RNA (shRNA) that specifically silences DG in cultured hippocampal neurons, we found that DG knockdown exerted an inhibitory effect on dendritic tree growth and arborization. The structural changes were associated with activation of the guanosine triphosphatase (GTPase) Cdc42. The overexpression of DG promoted dendritic length and branching. Furthermore, exposure of the cultures to autoactivating matrix metalloproteinase-9 (aaMMP-9), a β-DG-cleaving protease, decreased the complexity of dendritic arbors. This effect was abolished in neurons that overexpressed a β-DG mutant that was defective in MMP-9-mediated cleavage. Altogether, our results indicate that DG controls dendritic arborization in vitro in MMP-9-dependent manner.